LOAD ANALYSIS AND EXPERIMENTAL RESEARCH OF IDLER SHAFT ON ROCKER ARM SHEARER - HAO ZhiYong; CHEN ZhiQiang; MAOJun (Jixie qiangdu)
In order to study the mechanical and load properties of idler shaft on rocker arm shearer under complicated conditions,used the shaft sensor to test the load of idler shaft on rocker arm under different conditions,and through the wireless module to store and transmit the real-time data,with some test data curves in Z and Y direction obtained. The analysis results show that the load of idler shaft is the largest when coal winning machine under the oblique cutting condition,the largest load of 33. 38 kN in Z direction,the largest load of 35. 60 kN in Y direction,and thoughtout the process,the load in Y direction always larger than Z direction. The results of the study provide a new way for the idler shaft load test and data support for the coal-rock identification method and the fault monitoring on rocker arm shearer,also has important guiding and significance for coal winning machine parts design and optimization.